A Fractional Crystallization Link between Komatiites, Basalts, and Dunites of the Palaeoproterozoic Winnipegosis Komatiite Belt, Manitoba, Canada. (12th May 2020) - Waterton, Pedro; Pearson, D Graham; Mertzman, Stanley A; Mertzman, Karen R; Kjarsgaard, Bruce A
Abstract: The rock type most commonly associated with komatiite throughout Earth's history is tholeiitic basalt. Despite this well-known association, the link between komatiite and basalt formation is still debated. Two models have been suggested: that tholeiitic basalts represent the products of extensive fractional crystallization of komatiite, or that basalts are formed by lower degrees of mantle melting than komatiites in the cooler portions of a zoned plume. We present major and trace element data for tholeiitic basalts (∼7·5 wt% MgO) and dunites (46–48 wt% MgO) from the Palaeoproterozoic Winnipegosis Komatiite Belt (WKB), which, along with previous data for WKB komatiites (17–26 wt% MgO), are utilized to explore the potential links between komatiite and basalt via crystallization processes. The dunites are interpreted as olivine + chromite cumulates that were pervasively serpentinized during metamorphism. Their major and immobile trace element relationships indicate that the accumulating olivine was highly magnesian (Mg# = 0·91–0·92), and that small amounts (4–7 wt% on average) of intercumulus melt were trapped during their formation. These high inferred olivine Mg# values suggest that the dunites are derived from crystallization of komatiite. The tholeiitic basalts have undergone greenschist-facies metamorphism and have typical geochemical characteristics for Palaeoproterozoic basalts, with the exception of high FeO contents. Their REE patterns are similar to Winnipegosis komatiites, although absolute concentrations are higher by a factor of ∼2·5. The ability of thermodynamic modelling with MELTS software to reproduce komatiite liquid lines of descent (LLD) is evaluated by comparison with the crystallization sequence and mineral compositions observed for Winnipegosis komatiites. With minor caveats, MELTS is able to successfully reproduce the LLD. This modelling is extended to higher pressures to simulate crystallization of komatiitic melt in an upper crustal magma chamber. All major and rare earth element characteristics of the tholeiitic basalts can be reproduced by ∼60 % crystallization of a Winnipegosis komatiite-like parental melt at pressures of ∼1·5–2·5 kbar at oxygen fugacities between QFM − 1 and QFM + 1, where QFM is the quartz–fayalite–magnetite buffer. Winnipegosis basalts have low Mg# values that are not in equilibrium with mantle peridotite. They therefore cannot represent primary mantle melts derived from cooler mantle than the komatiites, and require fractional crystallization processes in their formation. Furthermore, their trace element characteristics indicate a depth of melting indistinguishable from that of the Winnipegosis komatiites, and derivation from an identical depleted mantle source. All geochemical and geological evidence is therefore consistent with their derivation from a komatiitic melt, and the presence of a large komatiite-derived dunite body in the WKB provides evidence of extensive fractionation of komatiite in the upper crust. The observed uniform basalt compositions are interpreted as the result of a density minimum in the evolving komatiitic melt at temperatures between clinopyroxene and plagioclase saturation, with efficient extraction of melt from a mixture containing ∼60 % crystals. We conclude that the WKB basalts formed by fractional crystallization of a komatiitic parental melt, and suggest that this model may be more broadly applicable to other localities where komatiites and associated basalts show similar geochemical or isotopic characteristics.